Balanceamento de carga em aplicações web e replicação de dados com PostgreSQL - Silva, Anderson Fernando Ribeiro da (2015)
With the expansion of the Internet and the rise of new services offered, membership for new users using the various access devices, forced the developers and solutions providers to rethink the way and the techniques used in their products, in order to contemplate this and miscellany concurrently maintain quality. This demand dramatically increases the use of new high-performance equipment and bandwidth internet access, which forced the market choose to optimize services with the resources already available or invest in updating or acquisition of their data centers. This paper aims to prove that it is possible by employing various techniques of tuning and high availability, increased performance of current services of a given scenario with the implementation of several new safety features and demonstrate that in some cases with minor adjustments hardware, it is possible to suppress equipment, thereby, reduce infrastructure costs.